2007
DOI: 10.1590/s1806-37132007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da resposta de pacientes asmáticos com refluxo gastroesofágico após terapia com pantoprazol: estudo prospectivo, randomizado, duplo cego e placebo-controlado

Abstract: In this study, the effective treatment of GERD improved patient quality of life, and the symptoms of asthma significantly decreased in the group that received the medication. There were no changes in pulmonary function parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Recently, in a randomized, prospective study, we demonstrated that treatment of GER with a proton pump inhibitor significantly improved the quality of life and the symptom scores of asthma patients with GER. (12) Histologically, two forms of bronchiolitis obliterans have been identified in lung transplant recipients. A relatively acellular form, consisting of a fibrosing process that is limited to the terminal bronchioles, and another form that is associated with microaspiration, represented by a focal, cellular inflammatory process that extends into the distal alveolar spaces.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in a randomized, prospective study, we demonstrated that treatment of GER with a proton pump inhibitor significantly improved the quality of life and the symptom scores of asthma patients with GER. (12) Histologically, two forms of bronchiolitis obliterans have been identified in lung transplant recipients. A relatively acellular form, consisting of a fibrosing process that is limited to the terminal bronchioles, and another form that is associated with microaspiration, represented by a focal, cellular inflammatory process that extends into the distal alveolar spaces.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in lung function, symptoms and quality of life have been reported in a few studies of PPI treatment in patients with asthma and comorbid GERD 1 , 50 54 . However, other studies reported no measurable improvement in asthma control 48 , 55 .…”
Section: Gastro-oesophageal Reflux (Gerd)mentioning
confidence: 97%
“…Uma revisão dos estudos de tratamento cirúrgico do RGE, que incluiu 417 pacientes com asma que haviam sido operados, encontrou redução dos sintomas de asma, do uso de medicamentos para asma e melhora da função pulmonar em 79, 88 e 27%, respectivamente (FIELD; GELFAND; MCFADDEN, 1999). Santos et al (2007a) realizaram um estudo, onde foi possível observar que pacientes com asma que receberam terapia com pantoprazol tiveram melhora no escore de sintomas respiratórios e de qualidade de vida, mas não nos parâmetros de função respiratória.…”
Section: Discussionunclassified